2010
DOI: 10.1177/1066480710364320
|View full text |Cite
|
Sign up to set email alerts
|

Filial Therapy With Monolingual Spanish-Speaking Mothers: A Phenomenological Study

Abstract: This article describes a phenomenological study of filial therapy with monolingual, Spanish-speaking mothers living in the United States. Four mothers participated in a 5-week training in filial therapy. Data from the interviews revealed four emergent themes. These include (a) challenges in integrating play therapy skills in everyday life, (b) empowerment from group support, (c) changes in the mother-child relationship, and (d) impact on the child's behavior. Multicultural considerations and implications for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…Similar to other studies that emphasized the importance of group process and social support for filial therapies (Attree, 2005; Edwards et al, 2007; Sangganjanavanich et al, 2010), this current study also indicated that group counseling processes enhanced the parent’s experiences. At the start of the sessions, some participants seemed hesitant to share their family life with one another and with the facilitators.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to other studies that emphasized the importance of group process and social support for filial therapies (Attree, 2005; Edwards et al, 2007; Sangganjanavanich et al, 2010), this current study also indicated that group counseling processes enhanced the parent’s experiences. At the start of the sessions, some participants seemed hesitant to share their family life with one another and with the facilitators.…”
Section: Discussionsupporting
confidence: 87%
“…Prior qualitative CPRT studies have documented changes in parents’ perceptions of the parent–child relationship such as listening to the child (Sangganjanavanich et al, 2010), paying attention to the child’s needs (Edwards, Sullivan, Meany-Walen, & Kantor, 2010), and increasing parental empathy (Edwards et al, 2007). This increased awareness and understanding of the child’s emotions were also meaningful for the parents who participated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the most rigorous outcome research studies have consistently revealed support for filial therapy in decreasing child behavior problems, decreasing parent-child relationship stress, and improving the empathic responsiveness of parents toward their children (see Bratton, Landreth, & Lin, 2010). Several researchers performing qualitative analyses of filial therapy have noted that parents reported improved parent-child relationships (Bavin-Hoffman, Jennings, & Landreth, 1996;Edwards, Ladner, & White, 2007;Edwards, Sullivan, MeanyWalen, & Kantor, 2010;Foley, Higdon, & White, 2006;Garza, Kinsworthy, & Watts, 2009;Kinsworthy & Garza, 2010;Lahti, 1992;Sangganjanavanich, Cook, & Rangel-Gomez, 2010;Solis, Meyers, & Varjas, 2004;West, 2010;Wickstrom, 2009). In addition, qualitative studies conducted by BavinHoffman, Jennings, and Landreth (1996), Lahti (1992), and Wickstrom (2009) have resulted in findings that are suggestive of potential changes occurring in the family as a whole.…”
Section: A Solution In Common: Both/andmentioning
confidence: 99%